John Cassavetes' A woman under the influence - Harwood, Bo ca. 20. Jh (Criterion collection, 2004)
A drama detailing the emotional breakdown of a suburban housewife and how her family struggles to save her from herself.
Bildformat 1.85:1 (enhanced for 16:9 widescreen TVs). - New high-definition digital transfer, with restored image and sound
Orig.: USA 1974
Enth. audio commentary by longtime Cassavete collaborators Mike Ferris (camera operator) and Bo Harwood (sound recordist, composer) ; new video conversation between actors Gena Rowland and Peter Falk ; audio interview with Cassavetes by film historian Michel Ciment and Michael Wilson conducted in 1975 ; stills gallery featuring rare behind-the-scenes production photos
Keywords: Middle class women -- United States -- Psychology -- Drama.; Housewives -- United States -- Psychology -- Drama.; Feature films.; Man-woman relationships -- United States -- Drama; Psychologie; Frau; Mittelstand; Zweierbeziehung; Hausfrau; USA; Film; DVD-Video; DVD-video discs; Feature films; Feature films - United States; Fiction films; Video recordings for the hearing impaired